THE IMPACT OF TOURIST VISITS AND REGIONAL ORIGINAL INCOME ON THE HUMAN DEVELOPMENT INDEX - Jauhariyah, Nur Anim; Syafa’at, Ahmad Munib; Budiywono, Eko; Munawir, Munawir; Khusnudin, Imam; Aini, Aula Izatul (International Conference on Humanity Education and Society (ICHES), 2024)
Abstract Tourism is a promising sector in increasing people's income, but what is the impact of tourist visits and local income on the human development index as a measure of quality progress in the area. The aim of this research is to analyze the impact of the large contribution of tourist visits and local revenue in increasing the human development index in Banyuwangi Regency. This research uses a quantitative approach by analyzing secondary data sourced from the Central Statistics Agency. The research results show that the influence of tourist visits and local income on the human development index is significant with a determinant coefficient value of 90.4%. The high coefficient value indicates that tourist visits and local income are variables that can increase the Human Development index in Banyuwangi Regency.